A Case Report of Home-Based Cognitive-Behavioural Treatment for Late-Onset Post-Traumatic Stress Disorder, Triggered by Mask-Wearing in the Context of the COVID-19 Pandemic. (December 2022) - Hanafi, Adham
A small but clinically significant number of people experience delayed-onset Post-traumatic stress disorder (PTSD); symptoms of trauma years after the events which are now being re-experienced. The following case report describes the use of the cognitive-behavioural treatment for PTSD with a woman experiencing flashbacks to domestic abuse endured more than 20 years ago. Mask-wearing mandated as a result of the COVID-19 pandemic triggered non-contextualised memories of life-threatening physical violence by an abuser who covered his face. She had been managing her flashbacks and intrusive thoughts with both behavioural and experiential forms of avoidance. An 18-session intervention was provided in her own home due to physical health difficulties. Treatment focused on managing hyper-arousal, reducing thought suppression, in-vivo exposure, stimulus-discrimination and re-contextualising traumatic memories. Regular outcome measurements were kept and results are presented as a single-case experimental design in 'AB' format (i.e. baseline period pre intervention). Symptoms of trauma fell to levels non-indicative of PTSD and speak to the evidence base for this modality, even when applied to delayed-onset difficulties in a non-traditional therapy setting. This conclusion is lent extra credence by an experimental design with good internal validity.